Deficiency in intestinal epithelial O‐GlcNAcylation predisposes to gut inflammation. Issue 8 (25th June 2018) - Zhao, Ming; Xiong, Xiwen; Ren, Kaiqun; Xu, Bing; Cheng, Meng; Sahu, Chinmayi; Wu, Kaichun; Nie, Yongzhan; Huang, Zan; Blumberg, Richard S; Han, Xiaonan; Ruan, Hai‐Bin
Abstract: Post‐translational modifications in intestinal epithelial cells (IECs) allow for precise control in intestinal homeostasis, the breakdown of which may precipitate the pathological damage and inflammation in inflammatory bowel disease. The O‐linked β‐N‐acetylglucosamine (O‐GlcNAc) modification on intracellular proteins controls diverse biological processes; however, its roles in intestinal homeostasis are still largely unexplored. Here, we found that levels of protein O‐GlcNAcylation and the expression of O‐GlcNAc transferase (OGT), the enzyme adding the O‐GlcNAc moiety, were reduced in IECs in human IBD patients. Deletion of OGT specifically in IECs resulted in disrupted epithelial barrier, microbial dysbiosis, Paneth cell dysfunction, and intestinal inflammation in mice. Using fecal microbiota transplantation in mice, we demonstrated that microbial dysbiosis although was insufficient to induce spontaneous inflammation but exacerbated chemical‐induced colitis. Paneth cell‐specific deletion of OGT led to Paneth cell dysfunction, which might predispose mice to chemical‐induced colitis. On the other hand, the augmentation of O‐GlcNAc signaling by inhibiting O‐GlcNAcase, the enzyme removing O‐GlcNAcylation, alleviated chemical‐induced colitis. Our data reveal that protein O‐GlcNAcylation in IECs controls key regulatory mechanisms to maintain mucosal homeostasis. Synopsis: Intestinal epithelial cells (IECs) control multiple layers of intestinal homeostasis. IEC‐specific O‐GlcNAcylation‐deficient mouse is a multi‐hit model for inflammatory bowel disease (IBD). Restoring O‐GlcNAcylation levels protected mice from chemical induction of inflammation. Levels of protein O‐GlcNAcylation were reduced in IECs in human IBD patients. IEC‐specific deficiency in O‐GlcNAcylation resulted in permeable epithelial barrier, Paneth cell dysfunction, microbial dysbiosis, and ultimately intestinal inflammation in mice. Elevating O‐GlcNAcylation levels increased barrier function and protected mice from chemically induced inflammation. Abstract : Intestinal epithelial cells (IECs) control multiple layers of intestinal homeostasis. IEC‐specific O‐GlcNAcylation‐deficient mouse is a multi‐hit model for inflammatory bowel disease (IBD). Restoring O‐GlcNAcylation levels protected mice from chemical induction of inflammation.